Answer:
D
Step-by-step explanation:
From the figure, the transformation that can be applied to the blue figure to create the red figure has the rule:
[tex](x,y)\rightarrow (-x,y)[/tex]
Now,
1. Reflection across the line y=-x has the rule
[tex](x,y)\rightarrow (-y,-x)[/tex]
2. Rotation 270° counterclockwise around the origin has the rule
[tex](x,y)\rightarrow (y,-x)[/tex]
3. Reflection across the line y=-x, and then rotation 270° counterclockwise around the origin has the rule
[tex](x,y)\rightarrow (-y,-x)\rightarrow (-x,y)[/tex]
As you can see, given transformation is equivalent to the sequense of transformations from option D